Hubungan Antara Pembuatan Keputusan Konsumen Dengan Kesetiaan Merek - Kamarudin, Jamaludin; Nursiah, Nursiah (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2023)
A number of empirical literature and research results have explained that brand loyalty is a conscious or unconscious consumer decision which is expressed through behavior or intention to repurchase a brand continuously, it occurs because consumers feel that the brand offers actual product features, image, or level of quality at a real price. This paper aims to explore theoretical and empirical frameworks about the effect of shopping orientation, buying criteria and self-image on brand loyalty. The research model that will be used is a replication of the model developed by. by Oh. J and Fiorito. S.S (2002) entitled "Korea woman's Clothing Brand loyalty". The resulting model identified 3 independent variables namely: shopping orientation, purchasing criteria and self-image and 1 dependent variable namely: brand loyalty. The model was analyzed using multiple regression methods. The results of this research show that multiple regression can explain the factors that influence brand loyalty. Based on a sample of 100 respondents from 4 hypotheses, it shows that shopping orientation, purchasing criteria and self-image have a positive effect on brand loyalty.